Cerebrovascular Involvement in Systemic Sclerosis - Maurizio Cutolo; Tamara Vojinovic; Sabrina Paolino; Rosanna Campitiello; Vanessa Smith (ACR Open Rheumatology)
Systemic sclerosis (SSc) is a chronic autoimmune rheumatic disease characterized by vascular damage, immune system dysregulation and fibrosis. The hallmark features include microvascular alterations and progressive tissue fibrosis, affecting skin, internal organs as well central and peripheral nervous system, adding to the disease's complexity and influencing overall outcomes. Of note, SSc has also been linked to macrovascular and cardiovascular involvement, including cerebrovascular damage as observed in stroke. Indeed, advanced neuroimaging is highly recommended for assessing cerebrovascular status in overt SSc to evaluate the complex interactions between cerebrovascular dysfunction and brain tissue damage and/or inflammation. Cerebral vasospasm detected by angiography, as well as an increase in subclinical cerebrovascular atherosclerosis observed by ultrasonography (carotid intimal medial thickness), are predictive for elevated stroke risk. Furthermore, a significant brain hypoperfusion detected by magnetic resonance imaging, along with white matter focal and/or diffuse signal abnormalities in SSc, have been found associated with concomitant peripheral microvascular damage detectable by “Active” and “Late” nail fold video capillaroscopy scleroderma patterns. Finally, the presence of calcifications in small arteries and arterioles found postmortem in the brain of SSc patients reinforces the hypothesis that SSc is associated with brain vascular remodeling. Furthermore, the current state of art shows an increased risk of cerebrovascular events in the SSc, confirmed by neuroimaging. Given the lack of updated comprehensive reviews on cerebrovascular involvement in SSc, we gathered the most relevant evidence on central nervous system damage, highlighting the underlying mechanisms, clinical implications, and potential advantages that neuroimaging may provide for its early detection.